HOW TO CREATE TELEMEDICINE EASILY IN PSYCHIATRY PRACTICE IN A COMMUNITY (MALAYSIA AND INDONESIA) - Nur Alia Syazwani; Zuhrotun Ulya (Journal of Psychiatry Psychology and Behavioral Research, 2020)
Telemedicine is an emerging industry with the ability to revolutionize healthcare delivery for the benefit of consumers, providers and payors. In general, it is a common concept which is used to define various aspects of healthcare at a distance. Telemedicine has been revealed as one potential solutions to some of the medical dilemmas that are faced by many developing countries. In recent years, the burden of caregiving for mental illness service users has been alarming due to the lack of resources in mental health services. The problem of treatment for mental illness in Malaysia and Indonesia is now becoming more complicated with people who have different attitudes and views. In this paper, we will discuss the current state and embracement of telemedicine in psychiatry (telepsychiatry) Â in developing countries in South-East Asia (SEA) in general, with Malaysia and Indonesia in particular.Â Keywords: telemedicine, telepsychiatry, psychiatry, healthcare, community, Malaysia, Indonesia